Fibroblast growth factor receptor 1 gene (FGFR1) expression in serous ovarian tumors (Annals of Medical Research, 2024)
Aim: The aim of this study was to evaluate the ovarian serous surface epithelial tumors in terms of FGFR1 expression and to evaluate the differences in expression of serous cystadenomas, borderline serous tumor/atypical proliferative serous tumors, low-grade and high-grade serous carcinomas.Materials and Methods: A hundred patients diagnosed with serous cystadenomas, borderline serous tumor/atypical proliferative serous tumors (BST), low-grade (LGSOC) and high-grade serous ovarian carcinomas (HGSOC) between 2010-2020 in our pathology laboratory were included in the study. In these cases, real-time PCR and immunohistochemistry were performed on sections from paraffin blocks.Results: In our study, it was determined that FGFR1 gene expression was statistically significantly increased in HGSOC cases compared to the BST/ LGSOC group and the SC group. Although there was a difference between the BST/ LGSOC group and the SC group, no statistical significance was found.Conclusion: FGFR1 expression was significantly increased in HGSOC cases. This finding has led to the conclusion that angiogenesis inhibition by FGFR inhibition may be a treatment option in HGSOC cases.
Keywords: Ovarian neoplasms; Polymerase chain reaction; Immunohistochemistry; Fibroblast growth factor